Parental exposure to microcystin-LR induced thyroid endocrine disruption in zebrafish offspring, a transgenerational toxicity. (November 2017) - Cheng, Houcheng; Yan, Wei; Wu, Qin; Liu, Chunsheng; Gong, Xiuying; Hung, Tien-Chieh; Li, Guangyu
Abstract: Microcystin-LR is the most poisonous and commonly encountered hepatotoxin produced by cyanobacteria in an aquatic ecosystem, and it may cause thyroid dysfunction in fish. The present study aimed to reveal the effects of transgenerational toxicity of MCLR on the thyroid endocrine system under sub-chronic exposure conditions. Adult zebrafish (F0) were exposed to environmentally relevant concentrations (1, 5 and 25 μg/L) of MCLR for 45 days. The produced F1 embryos were then tested without further MCLR treatment. In the F0 generation, exposure to 25 μg/L MCLR reduced thyroxine (T4) but not 3, 5, 3′-triiodothyronine (T3) levels in females, while the T4 and T3 levels were unchanged in males. After parental exposure to MCLR, we observed a decreased hatching and growth retardation correlated with reduced thyroid hormone levels in the F1 offspring. The gene transcription and protein expression along the hypothalamic-pituitary-thyroid axis were detected to further investigate the possible mechanisms of MCLR-induced thyroid disruption. Our results indicated MCLR could disturb the thyroid endocrine system under environmentally relevant concentrations and the disrupting effects could be remarkably transmitted to its F1 offspring. We regard these adverse effects as a parental transgenerational toxicity of MCLR. Graphical abstract: Highlights: Parental exposure to environmentally relevant concentrations of MCLR induced serious growth retardation in F1 larvae. Parents exposed to environmentally relevant concentrations of MCLR obviously perturbed THs in F0 and F1 generations. The decreased thyroid hormone levels in F1 larvae was associated with the altered expression of HPT axis related genes. Parental thyroid dysfunction contributed to the decrease of thyroid hormone levels in F1 larvae. Abstract : Parental exposure to MCLR for 45 days induced thyroid endocrine disruption in both F0 and F1 generations which may cause growth retardation in F1 larvae.